An Investigation into the Regulation of Artificial Intelligence in Financial Markets Using Organisational Responses and Legislative Barriers - Ragavendran, V.A; Bhavesh Jain, R (International Journal of Engineering and Management Research, 2026)
The swift adoption of Artificial Intelligence has completely transformed how trading is conducted, how risks are managed, and the decisions made in financial markets. However, this transformation now raises significant financial and legal challenges. Issues such as market manipulation, clarity over algorithm transparency, ethical use of AI, and compliance with prevailing financial regulations have gained the attention of major concerns for businesses and governments. This work explores how legal frameworks around AI in financial markets change, including under international laws, methods to train the AI system, and how the rules are enforced. It also demonstrates how financial regulators can achieve market stability, protect investors, and ensure that AI is responsibly used. The paper addresses that regulation should be done in a way that is neither unfair nor one-sided, to accord substantial impetus to innovation at low risk.